Modeling and Simulation of Supersonic Natural Gas Dehydration using De Laval Nozzle - Wong , Mee Kee (Universiti Teknologi Petronas, 2009)
The purpose of this report is to provide an overview of the writer’s Final Year Project. Current techniques in dehydration of natural gas, such as absorption, adsorption and membrane require relatively large facilities, a large investment, complex mechanical work, and the possibility of having a negative impact on the environment. Separation with supersonic flow is proposed as a solution to some of the disadvantages of conventional methods. The objectives of the project is to perform simulation which model natural gas flow through a convergent-divergent nozzle which separates water from natural gas and study pressure and temperature drop as well as the effectiveness of the separation. FLUENT and GAMBIT are the major tool used in running the simulation. Simple explanation on the methods is provided in this report. Gas is accelerated up to velocities exceeding the sound propagation velocity in gas through a convergent-divergent nozzle due to transformation of a part of the potential energy of flow to kinetic energy the gas is cooled greatly. The result of the simulation shows velocity of gas increases significantly at the choke, resulting in temperature drop which condenses water vapour in the gas mixture. By removing water liquid droplets, water content in system can be reduced. Temperature, pressure, velocity and component mass fraction profiles are included in the report. Furthermore, effects of different inlet mass flow rate are studied. Higher inlet mass flow rate increases temperature drop, hence more water vapour is condensed and lower water content left in natural gas. For effective separation, sufficient inlet mass flow rate is required to achieve sonic flow in a 3-inch pipeline. Recommendations for future work expansion and continuation are provided at the end of the report.